Farmers’ Rationality and Skill Preparedness to Answer the Challenges of Industrial Revolution 4.0 towards Society 5.0: A Case Study in Serang - Mirajiani, Mirajiani (Universitas Negeri Semarang, 2022)
Industrial revolution 4.0 towards society 5.0 in the agricultural sector creates complex challenges that demand preparedness of farmer human resources that possess certain rationalities compatible to current development and skill preparedness with various cultural adaptation efforts. The study aims to explore the farmers’ rationality and skill preparedness to answer the challenges of industrial revolution 4.0 towards society 5.0. The research was conducted in Serang City. The research results indicate that the application of agriculture 4.0 is still in the preparation stage. Socio-economic-cultural changes foster agripreneurship system amongst farmers and become an initial capital to answer challenges of the agricultural 4.0. Commercialization and modernization of agriculture brought by social changes and development have shifted the farmers’ rationality map from value rationality to means-end rationality following several development stages passed. Farmers’ creativity is still limited due to the lack of competitiveness and knowledge capacity with productivity-improvement orientation, but not yet efficiency-based. The farmers are relatively adaptive and flexible with the existing changes.